The hidden histories of war crimes trials - Heller, Kevin Jon; Simpson, Gerry J. (2014)
Several war crimes trials are well-known to scholars, but others have received far less attention. This book assesses a number of these little-studied trials to recognise institutional innovations, clarify doctrinal debates, and identify their general relevance to the development of international criminal law.